Appraisal of Antioxidant Potential in Broccoli Microgreens under Different Drying Techniques Utilizing In Vitro and in Silico Methods - Tallei, Trina Ekawati; Wungouw, Herlina Ineke Surjane; Kepel, Billy Johnson; Fatimawali, Fatimawali; Celik, Ismail; Niode, Nurdjannah Jane; Barasarathi , Jayanthi (Heca Sentra Analitika, 2025)
Broccoli microgreens, rich in bioactive compounds, offer health benefits aligned with SDG 3: “Good Health and Well-Being.” Their antioxidants combat oxidative stress tied to chronic diseases, but drying can affect their activity. This study assessed the antioxidant capacities of fresh, microwave-dried, and air-fryer-dried broccoli microgreens using in vitro (DPPH assay) and in silico (molecular docking and dynamics) methods. The microgreens were cultivated under controlled conditions and dried using microwave and air-fryer techniques. Antioxidant activity was evaluated using the DPPH assay using ethanolic extracts. The bioactive compounds of fresh microgreens, detected through GC-MS, were analyzed in silico to evaluate their interactions with the target proteins CYP2C9 and NOX2. The findings revealed that air-fryer-dried microgreens demonstrated the highest DPPH activity, followed by fresh microgreens, while microwave-dried samples exhibited the lowest activity. GC-MS analysis of fresh samples revealed the presence of various compounds, including acids, ketones, sulfides, heterocycles, alcohols, esters, aromatic compounds, phthalate ester, and aldehydes. Molecular docking revealed strong interactions of certain compounds in fresh samples and CYP2C9 and NOX2, suggesting therapeutic potential against oxidative stress. Molecular dynamics simulations (MDS) showed stable binding for the CYP2C9-Methyl myristate complex, while the NOX-(Z)-1,2-Diphenylethene complex displayed weaker stability. In conclusion, broccoli microgreens show potential in mitigating oxidative stress, with air-fryer drying slightly enhancing their antioxidant activity. The antioxidant capacity of fresh microgreens is comparable to that of air-fryer-dried microgreens. In silico analyses demonstrate stable interactions between compounds in fresh microgreens and key proteins implicated in oxidative stress.